Relación de las prácticas ambientales, sociales y de gobernanza (ESG) en el desempeño empresarial: una evidencia empírica para empresas del S&P 500 - Flores, Alejandro; Rubiños, Cathy; Peña Contreras, Jorge (Pontificia Universidad Católica del Perú, 2025)
This study analyzes the relationship between ESG practices and business performance in companies belonging to the S&P 500 index during the period 2015-2024, using panel data models with fixed effects. A negative effect of ESG on market capitalization is observed, while no significant effects are identified on return on assets. By conducting a heterogeneity analysis through sectoral interactions and quintile segmentation, it is contrasted that the effect is not uniform. These findings suggest that the effects of ESG depend on the main activity and market capitalization, highlighting benefits in technological companies and costs in industrial companies. Likewise, in the case of companies with lower capitalization, the effect turns out to be positive in the most representative activities of the sample. Our recommendations emphasize the need for companies to adopt differentiated ESG strategies, considering their sectoral context and market value.

Este estudio analiza la relación entre las prácticas ESG y el desempeño empresarial en empresas pertenecientes al índice S&P 500 durante el periodo 2015-2024, utilizando modelos de datos de panel con efectos fijos. Se observa un efecto negativo de las prácticas ESG sobre la MC, mientras que no se identifican efectos significativos en el retorno sobre activos. Al realizar un análisis de heterogeneidad mediante interacciones sectoriales y segmentación por quintiles, se contrasta que el efecto no es uniforme. Estos hallazgos sugieren que los efectos del ESG dependen de la actividad principal y de la capitalización bursátil, destacando beneficios en empresas tecnológicas y costos en empresas industriales. Asimismo, en el caso de las empresas de menor capitalización, el efecto resulta positivo en las actividades más representativas de la muestra. Nuestras recomendaciones enfatizan la necesidad de que las empresas adopten estrategias ESG diferenciadas, considerando su contexto sectorial y su valor bursátil.
Relationship between environmental, social, and governance (ESG) practices and business performance: empirical evidence for S&P 500 companies
Keywords: ESG; Financial performance; Corporate sustainability; Corporate social responsability; ESG; Desempeño financiero; Sostenibilidad corporativa; Responsabilidad social empresarial; ESG; Desempenho financeiro; Sustentabilidade corporativa; Responsabilidade social corporativa; https://purl.org/pe-repo/ocde/ford#5.02.04